Amyotrophic lateral sclerosis and the innate immune system: protocol for establishing a biobank and statistical analysis plan. Issue 8 (5th August 2020) - Kjældgaard, Anne-Lene; Pilely, Katrine; Olsen, Karsten Skovgaard; Lauritsen, Anne Øberg; Pedersen, Stephen Wørlich; Møller, Kirsten; Garred, Peter
Abstract : Introduction: Amyotrophic lateral sclerosis (ALS) is a devastating, progressive disease that causes degeneration of the motor neurons leading to paresis of the bulbar and the skeletal musculature. The pathogenesis of ALS remains unknown. We will test the hypothesis that the complement system is involved in the pathophysiology of ALS. This protocol article describes our efforts to establish a national Danish ALS biobank. The primary aim is to obtain biological material from patients with ALS for the current study as well as for future studies. Methods and analysis: We intend to establish an observational ALS biobank; some of the material from this biobank will be used for a prospective, observational case–control study. The participants are patients with ALS, neurologically healthy controls and non-ALS neurological controls. Each participant consents to be interviewed and to donate blood and cerebrospinal fluid to the biobank. Analysis of the complement system will be carried out on the three groups of patients and compared. Ethics and dissemination: The project has been approved by the Committees on Health Research Ethics in the Capital Region of Denmark (Approval number H-16017145) and the Danish Data Protection Agency (file number 2012-58-0004). All results will be published in peer-reviewed, medical journals and presented at scientific conferences. Trial registration number: NCT02869048